Analisis Laporan Keuangan Guna Mengukur Kinerja Keuangan Pada PT. ACE Hardware Indonesia Tbk - Ayudia Febrihartini; Dinda Agung Trisna; Ratih Kusumastuti (Pusat Riset dan Inovasi Nasional, 2023)
The financial statements of a company are important in its use. Because, with financial reports, company management and external parties need these reports to make a decision. The main step in carrying out this decision-making is of course by first analyzing the financial statements, in order to find out whether a company's finances are healthy or not, and can also assess how the company's performance is through its financial reports. This study aims to be able to find out how the financial performance at PT. ACE Hardware Indonesia Tbk reviewed through analysis of financial ratios. The method used in this research is descriptive method by measuring liquidity ratios, solvency ratios, profitability ratios and activity ratios. Data and information sources were taken from the Indonesia Stock Exchange and parties that have previously published this analysis.